International Legal Framework for the Protection of Personal Rights in the Era of Digitalization (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In this article, the extent to which the protection of personal rights in the digital space is reflected in national and foreign legislation is deeply and comprehensively analyzed. Also, the works being carried out in this field and their effectiveness have been mentioned. In today's globalization process, cyberbullying and other similar threats that can be encountered in the protection of human rights in the Internet system are analyzed. The main problems that countries may encounter in the field of protection of human rights in the Internet system have been analyzed and appropriate proposals have been developed for solving these problems.